Territoriality, visionaries, and nomadic citizenships in Vagos sin tierra by Renée Ferrer and Las Marías de los Toldos by Aurora Venturini - Paula Daniela Bianchi (Estudios de Teoría Literaria)
This article proposes to reflect on the critical categories of land, territory, and territoriality in relation to peripheral bodies, nomadic citizenships, and displacement in border zones in the novels Vagos sin tierra (1999) by Paraguayan writer Renée Ferrer, which takes place in the Concepción, and Las Marías de Los Toldos (1991) by Argentine writer Aurora Venturini, which focuses on Los Toldos and La Plata, places relatively close to the cities of Asunción and Buenos Aires, respectively. They plan the construction of a literature that seeks to escape neoliberalism and the logic that generates global “exclusion zones” (Pratt) based on the transit of these figurations that increasingly move away from urban centers towards a “promised land” in search of habitability of the land, although they always remain in unfavorable areas and with citizenships in crisis. Mary Louise Pratt (2018) recognizes that the stories of the nineties obey a planetary and imperial reordering, in this sense, we will see how these narratives constitute timeless characters anchored, at the same time, in a precise historical temporality and a diffuse shared futurity in a nomadic territoriality.